Activation of the CD95 (APO-1/Fas) system in T cells from human immunodeficiency virus type-1-infected children - Bäumler, Caroline Beatrix; Bonier, Thomas; Herr, Ingrid; Benner, Axel; Krammer, Peter H.; Debatin, Klaus-Michael (Blood, 1996)
Increased apoptosis of CD4+ T cells is considered to be involved in CD4+ T-cell depletion in human immunodeficiency virus type-1 (HIV-1)-infected individuals progressing toward acquired immunodeficiency syndrome (AIDS). We have recently shown that CD95 (APO-1/Fas) expression is strongly increased in T cells of HIV-1-infected children. In this report we provide further evidence for a deregulated CD95 system in AIDS. CD95 expression in HIV-1+ children is not restricted to previously activated CD45RO+ T cells but is also increased on freshly isolated naive CD45RA+ T cells. In addition, specific CD95-mediated apoptosis is enhanced in both CD4+ and CD8+ T cells. Furthermore, levels of CD95 ligand mRNA are profoundly increased. Specific T-cell receptor/CD3-triggered apoptosis in HIV-1+ children is more enhanced in CD8+ than in CD4+ T cells. Accelerated activation induced cell death of T cells could partially be inhibited by blocking anti-CD95 antibody fragments. These data suggest an involvement of the CD95 receptor/ligand system in T-cell depletion and apoptosis in AIDS and may open new avenues of rational intervention strategies.
Elektronische Reproduktion der Druck-Ausgabe 14. Dezember 2020
Gesehen am 24.09.2024